2016
DOI: 10.2214/ajr.15.15813
|View full text |Cite
|
Sign up to set email alerts
|

Classifier Model Based on Machine Learning Algorithms: Application to Differential Diagnosis of Suspicious Thyroid Nodules via Sonography

Abstract: The machine learning algorithms underperformed with respect to the experienced radiologist's readings used to construct them, and the RBF-NN outperformed the other machine learning algorithm models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…The quality of the included studies is summarized in online supplementary Table 2. The risk of bias from patient selection was judged to be high or unclear in 13 of the included studies: 4 studies limited the nodule size within a certain scope [16,17,21,25]; 5 studies excluded difficult-to-diagnose nodules [15,[25][26][27]31]; and 4 studies were unclear about whether there were selected co-horts and inappropriate exclusions [14,19,23,29]. The risk of bias from the reference standard was considered to be unclear in 2 of the included studies [14,23].…”
Section: Methodological Quality Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of the included studies is summarized in online supplementary Table 2. The risk of bias from patient selection was judged to be high or unclear in 13 of the included studies: 4 studies limited the nodule size within a certain scope [16,17,21,25]; 5 studies excluded difficult-to-diagnose nodules [15,[25][26][27]31]; and 4 studies were unclear about whether there were selected co-horts and inappropriate exclusions [14,19,23,29]. The risk of bias from the reference standard was considered to be unclear in 2 of the included studies [14,23].…”
Section: Methodological Quality Of the Included Studiesmentioning
confidence: 99%
“…The flow diagram of the literature search is shown in Figure 1. Nineteen studies with 4,781 nodules used in external validation sets were included in the study, including 6 studies on classic machine learning-based CAD sys-DOI: 10.1159/000504390 tems [14][15][16][17][18][19] and 13 studies on deep learning-based CAD systems [7,[20][21][22][23][24][25][26][27][28][29][30][31]. The general characteristics of the included studies are shown in Table 1, and the detailed characteristics are demonstrated in online supplementary Table 1 (see www.karger.com/doi/10.1159/000504390 for all online suppl.…”
Section: Literature Searches and Description Of Studiesmentioning
confidence: 99%
“…However, when the diagnostic performances of quantitative analysis and visual assessment by radiologists were compared in predicting thyroid malignancy, quantitative analysis showed relatively inferior diagnostic performance compared to traditional grayscale US . A number of machine learning algorithms using US images have been investigated for the differential diagnosis of thyroid nodules and have shown conflicting results when diagnostic performances were compared between these algorithms and visual assessment by radiologists . The convolutional neural network (CNN) is a typical type of deep learning technique with fully trainable models and is accepted as a state‐of‐the‐art method .…”
Section: Introductionmentioning
confidence: 99%
“…13,14 A number of machine learning algorithms using US images have been investigated for the differential diagnosis of thyroid nodules and have shown conflicting results when diagnostic performances were compared between these algorithms and visual assessment by radiologists. [15][16][17][18][19][20] The convolutional neural network (CNN) is a typical type of deep learning technique with fully trainable models and is accepted as a state-of-the-art method. 21,22 Ma et al 23 first attempted a CNN-based method to classify thyroid nodules and the method was shown to be eligible for thyroid nodule diagnosis, but their study did not enroll patients in a clinical setting and did not compare diagnostic performances between CNN and radiologists.…”
mentioning
confidence: 99%
“…After the introduction of many and different computational systems [76], a new class of applications has recently emerged in the health care debate: the decision support systems (DSS) that embed predictive models that have been developed by means of machine learning (ML) methods and techniques. These systems, which for the sake of brevity we will call ML-DSS, have recently raised a strong interest among the medical practitioners of almost every corner of the world in virtue of their high accuracy at an unprecedented extent [26,37], in some cases even allegedly capable of outperforming human experts (e.g., [50,93]). This is reflected by the stance of influential commentators and medical experts that have recently shared their thoughts from some of the most impacted journals of the medical community (e.g.…”
Section: Motivations and Backgroundmentioning
confidence: 99%